Breast asymmetries: Classification and systematic review - Susini, Pietro; Fidanza, Anastasia; Grimaldi, Luca; Nisi, Giuseppe; Cuomo, Roberto; Brogi, Mattia; Menichini, Giulio; Delcroix, Luca; Portincasa, Aurelio; Innocenti, Alessandro (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Several classification systems have been proposed for breast asymmetries (BAs) considering volume, shape, position, nipple-areola complex and inframammary fold. In addition, breast consistency should be considered as an additional topic. The latter, although poorly investigated, depends on the adipo-glandular ratio of each breast. Since fat and gland undergo different changes in response to specific stimuli, breasts with different consistency can behave differently over time, even in the same subject, potentially leading to asymmetry. The present review aims to propose a comprehensive classification system of BAs, including the minor forms, taking into account, among the common clinical features, the preoperative consistence of breast tissue.Methods: A PRISMA systematic review was carried out on the PubMed library from June 2004 to June 2024 searching for studies on BAs original classifications and management strategies.Results: Thirty-six articles and 3979 patients were included. Specifically, 26 papers on BAs management strategies and 10 articles on BAs original classifications.Conclusions: BAs of the NAC, the IMF and the breast cone can be distinguished into idiopathic or secondary and following quantitative (volume and projection) and qualitative parameters (shape, position and consistency). Consistency is particularly relevant for surgical stability of the results over time. Therefore, the preoperative evaluation should not be limited to a simple visual inspection but requires a careful palpatory comparison of each breast in order to assess any qualitative BAs and plan the appropriate strategy, aiming to improve surgical results and their long-term stability. (www.actabiomedica.it)